Sujeitos nulos em inglês L2 - Teixeira, Joana (Revista da Associação Portuguesa de Linguística, 2019)
The present article investigates the acquisition of a core syntactic property – the ungrammaticality of null subjects in English – by advanced and near-native learners whose first languages are European Portuguese (EP), a null subject language, and French, a non-null subject language. Two experimental tasks were used: an untimed drag-and-drop task and a speeded acceptability judgement task. Results show that French speakers behave target-like across all tasks and conditions, but EP speakers do not. At an advanced level, they fail to reject expletive and [-animate] null subjects in the speeded task. Crucially, at a near native level, EP speakers behave fully target-like across all conditions and tasks. These findings indicate that the syntax of subjects may exhibit significant developmental delays depending on first-second language combinations, but is completely acquirable. Developmental problems are argued to result from the misanalysis of (some of) the overt expletive subjects in the L2 input. This proposal is supported by an exploratory follow-up experiment, whose results are presented and discussed in the article.